Kualitas Orang Benar di Tengah Relativitas Postmodernisme - Samuel Wasikin; Verry Willyam (SANCTUM DOMINE: JURNAL TEOLOGI, 2023)
Today, Christianity is facing a decline in morals and faith in the era of progress and advancement. The current generation lacks an understanding of the importance of moral ethics in building healthy and proper relationships. The Post-Modernism era has brought a mindset of relativism, making it easier for people to weigh everything, including technology. The purpose of this article is to explore the meaning of the righteous person in Genesis 18:16-33 the relevance of the life righteous in the postmodern era. The method presented in this writing is by using the Narrative Criticism approach to the book of Genesis 18:16-33, where Abraham converses with God in his intercession for Sodom and Gomorrah. Abraham seeks to advocate for the "righteous people" so that God may spare the city, but the number he proposes is not fulfilled. And ultimately, the profound meaning of the "righteous people" is those who live according to divine law and have faith in God. In the postmodern era, views on truth are relative, but Abraham's story shows that God still values the existence of righteous individuals amidst moral decay. Believers need to uphold religious values and become examples that glorify God in facing the changes of time.